Column Chromatography Abetted Isolation of Aryl Naphthalene’s from Cleistanthus collinus by: A Novel Approach - Utane, Rajdip (Current Aspects in Pharmaceutical Research and Development Vol. 8, 2022)
Aryl naphthalene’s lignans are extracted by pet. ether from Cleistanthus collinus. Objective to study poisonous plant such as Cleistanthus collinus has contained biological potent Naphthalene. The bark, leaves, heartwood, fruits and other parts of this plant are rich in lignans cleistanone along with their lactones. Isolation of chemical constitutions by column chromatography, followed by TLC examination and Detection in iodine chamber with UV lamp or sprayer solution (CH2Cl2: CH3OH). The isolated arylnaphthalide lignans are cleistanone, diphyllin, cleistanthins A, C and D and 4-O-(30-O-methyl-b -D- glucopyranosyl)-diphyl lin.